Development of lead-free thin-film dielectrics for capacitor applications - Darbyshire, David Anthony (Cranfield University, 2010)
This PhD project aims to develop lead-free thin-film dielectric materials for fixed value, voltage tunable and high-k zipping variable capacitors using growth techniques that can be scaled for silicon batch fabrication. The thesis specifically details the growth and characterisation of barium zirconate titanate (BZT) and bismuth zinc niobate (BZN) dielectric thin films. Fixed value and tunable capacitors have been realised through the use of low and high permittivity dielectric thin film materials in both the amorphous and crystalline states. Planar devices fabricated using BZT and BZN dielectric thin films were grown by sol-gel and RF magnetron sputtering, respectively. The effects of different bottom electrodes were also investigated. Capacitors in a metal-insulator-metal (MIM) [metal-ferroelectric-metal (MFM) for BZT] structure have been fabricated to characterise the dielectric films at low frequency to 300 kHz. Cont/d.